1996
DOI: 10.1001/archneur.1996.00550110056012
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow Correlates of Apathy in Alzheimer Disease

Abstract: Background: Apathy is a pervasive noncognitive neuropsychiatric disturbance in Alzheimer disease, which causes significant caregiver distress. The neuroanatomical substrate of apathy is not well understood. Objective: To study the relationship between regional cerebral blood flow and the presence and severity of the personality disturbance, apathy, in individuals with Alzheimer disease. Design: Analysis of the relationship between regional cerebral blood flow as measured by single photon emission computed tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
138
4
5

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(157 citation statements)
references
References 27 publications
7
138
4
5
Order By: Relevance
“…This conclusion is supported by previous associations between apathy and dysfunction in prefrontal and anterior temporal brain regions (Okada et al, 1997;Craig et al, 1996). Cerebrovascular disease has previously been linked to depression in several studies of individuals with dementia (e.g., O'Brien et al, 2000;Hargrave et al, 2000).…”
Section: Discussionsupporting
confidence: 68%
“…This conclusion is supported by previous associations between apathy and dysfunction in prefrontal and anterior temporal brain regions (Okada et al, 1997;Craig et al, 1996). Cerebrovascular disease has previously been linked to depression in several studies of individuals with dementia (e.g., O'Brien et al, 2000;Hargrave et al, 2000).…”
Section: Discussionsupporting
confidence: 68%
“…Apathy is the most frequent and severe behavioral symptom in both MCI [1] and Alzheimer's disease (AD) [2,3] and may characterize a subset of MCI subjects at higher risk of progression to dementia [4][5][6][7]. The functional neuroanatomy of apathy has been studied primarily in AD patients, where it was found that bilateral frontal, temporal, and cingulate area hypoperfusion and hypometabolism are associated with apathy severity [8][9][10][11][12]. Several structural neuroimaging studies also demonstrated an association between apathy and loss of integrity of frontal regions in AD [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Its prevalence depends on the type of population studied, the diagnostic criteria and the type or severity of dementia. when diagnosed with the Neuropsychiatric Inventory (NPI) 15 in outpatient settings, apathy prevalence ranged from 55% 16 to 80% 17 , and from 36% 12 to 53.3% 18 in community based samples of Ad patients. van reekum and coworkers' pooled analysis found a point prevalence of 60.3% in outpatients with Ad 19 .…”
mentioning
confidence: 99%